Production of High Performance Eco-Composite Materials for Aerospace Applications - Aydın, Cihat; Aydın, Handan; Avcı, Sinan (Niyazi BULUT, 2025)
In today's aviation industry, the use of composite materials has reached 30%. Studies on composite materials continue intensively and these materials are seen as the only solution to meet the material requirements of developing technology. The features expected from composite materials produced for use in the defense industry are high strength, formability, corrosion resistance and vibration damping. In the wing and tail elements of military aircraft such as airplanes and helicopters, in aircraft armors and unmanned aerial vehicles, economical, easily produced and superior composite materials are preferred.
Keywords: Functional Materials; Fonksiyonel Malzemeler